Antioxidant potential of gotu kola leaf extract (Centella asiatica (L.) Urban) as an alternative to antihyperglycemic herbal drinks - Ida Ayu Manik Damayanti; Ni Wayan Sukma Antari; Sri Dewi Megayanti (Jurnal Pijar Mipa, 2022)
This study aims to determine the antihyperglycemic potential of Gotu kola leaf extract (Centella asiatica (L.) Urban as an alternative herbal drink in diabetic male white mice. This study was divided into four stages: extracting Gotu kola leaves using 96% ethanol as solvent, phytochemical screening, and testing antihyperglycemic activity. Male white mice were made diabetic by alloxan-induced. Mice were divided into five groups consisting of negative control (Aquadest), positive control (Glibenclamide 13 mg/Kg BW), dose 1 (200 mg Gotu kola extract/kg BW), dose 2 (400 mg Gotu kola extract/kg BW), dose 2 (400 mg Gotu kola extract/kg BW), 3 (600 mg Gotu kola extract/kg BW). The results of phytochemical screening showed that the Gotu kola leaf extract was positive for flavonoids and tannins. The analysis results on the Gotu kola leaf extract showed an IC50 value of 80.58 ppm, including strong antioxidant activity. The results of the antihyperglycemic activity test showed that diabetic male white mice were found to have decreased blood sugar levels on days 14 and 21 by respectively 24.3% and 41.6%; 25.4% and 42.3%; 37.8% and 55.3% after administration of Gotu kola leaf extract at P1, P2, and P3.